Bilateral Frontal Hemorrhagic Necrosis Associated with Acute Ethanol Poisoning on the Basis of Chronic Alcoholism: Case Report and Review of the Literature - İrem Taşcı; Meryem Bakır (Türk Nöroloji Dergisi, 2020)
Chronic alcoholism and acute ethanol poisoning have significant effects on the central nervous system. These effects can be divided into two groups. The first effect is the volume loss associated with a toxic effect on neurons mediated by neurotransmitters and/or receptors and electrolytes, and the secondary effects are associated with the sequela of liver cirrhosis such as hepatic encephalopathy and coagulopathies, and the problems in the gastrointestinal tract leading to impairment of vitamin uptake, ultimately leading to Wernicke-Korsakoff syndrome. Herein, we report a 68-year-old male patient who presented to the emergency room with confusion associated with acute ethanol poisoning on the basis of chronic alcoholism. A brain computed tomography (CT) scan revealed symmetrical hemorrhagic necrosis in bilateral frontal regions. In our case, vasculopathies and infectious etiology were excluded through cerebral and carotid vertebral CT angiography, examinations, and laboratory findings. Investigation of the cause of this atypical radiographic finding revealed that ethanol ingestion leads to increased risk for hypertension, as well as cerebral hemorrhage by resulting in coagulation dysfunction; it triggers P53- and neuron-specific enolase- mediated apoptosis and necrosis, thereby resulting in neuronal damage. Acute and chronic use of ethanol has specific effects on the frontal lobe of the brain. The findings are discussed in light of the relevant literature.